Chevron Bangladesh and impact of degree of financial leverage on profitability of Chevron and its global competitors - Rahman, Abul Khayar Mohammod Fazlur (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.